One jump at a time : my story - Chen, Nathan, 1999-; Park, Alice (Harper, an imprint of HarperCollinsPublishers, 2022)
The three-time World Champion, Olympic gold medalist, and the first Asian American man to stand at the highest podium in figure skating reflects on the events that led him to where he is today, in this testament to the love of family and the power of persistence, grit, and passion.